2011
DOI: 10.1056/nejmoa1013607
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Antiretroviral Therapy for HIV-1 Infection and Tuberculosis

Abstract: Background Antiretroviral therapy (ART) is indicated during tuberculosis (TB) treatment of patients infected with HIV-1, but the urgency to start ART at TB diagnosis for patients of varying levels of immune compromise is not known. Methods We conducted an open label, randomized study comparing immediate (within 2 weeks of TB treatment initiation) to early (8–12 weeks) ART among HIV-1 infected patients with CD4+ lymphocytes < 250/mm3 and suspected TB. The primary study endpoint was proportion of patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
449
3
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 488 publications
(489 citation statements)
references
References 21 publications
31
449
3
4
Order By: Relevance
“…506 Initiating antiretroviral therapy during tuberculosis treatment improves survival; 315,317 integrating tuberculosis and HIV care is costeffective; 507 early initiation of antiretroviral therapy in people with MDR tuberculosis and HIV substantially reduces mortality; 508 and, in patients with XDR tuberculosis and HIV, more deaths occur among those not receiving antiretroviral therapy. 509 Despite this overwhelming supportive evidence and guidelines for integration, implementation is scarce.…”
Section: Integration: One Patient One File One Health-care Workermentioning
confidence: 99%
“…506 Initiating antiretroviral therapy during tuberculosis treatment improves survival; 315,317 integrating tuberculosis and HIV care is costeffective; 507 early initiation of antiretroviral therapy in people with MDR tuberculosis and HIV substantially reduces mortality; 508 and, in patients with XDR tuberculosis and HIV, more deaths occur among those not receiving antiretroviral therapy. 509 Despite this overwhelming supportive evidence and guidelines for integration, implementation is scarce.…”
Section: Integration: One Patient One File One Health-care Workermentioning
confidence: 99%
“…All HIV‐infected children diagnosed with TB should also be started on ART; however, the optimal timing of ART initiation depends on the degree of immunocompromise. Adult RCTs showed significant reduction in mortality and progression to AIDS with earlier ART in patients with CD4 counts < 50 cells/μl (Starting ART at 3 Points in TB (SAPIT) 162, Cambodian Early versus Late Introduction of Antiretrovirals (CAMELIA) 163 and Immediate Versus Deferred Start of Anti‐ HIV Therapy in HIV ‐Infected Adults Being Treated for Tuberculosis (STRIDE) 164). A retrospective study in South African children, most of whom were severely immunocompromised with median CD4 percentage < 12%, also showed that delay of ART for longer than 2 months was associated with increased mortality and worse virological response 165.…”
Section: Coinfectionsmentioning
confidence: 99%
“…New drug development aims to shorten the TB treatment course with drugs that are easier to take, less toxic, cheaper, have fewer interactions and are effective in drug resistance, such as gatifloxacin, moxifloxacin, rifapentine and delamanid, which are in Phase III trials [102]. New evidence concerning the optimization of the timing of initiation of ART in HIV and TB coinfection has been provided by several studies (Camelia, ACTG 5221 and SAPiT studies [5][6][7]) essentially advising earlier ART commencement with advanced disease (i.e., CD4 <50 cells/µl) despite the increased risk of immune reconstitution disease. Major hurdles that still need to be overcome are the management of multidrug-resistant TB and the broadening of ART regimens that can be safely and effectively used with anti-TB therapy.…”
Section: Tb: New Drug and Treatment Strategiesmentioning
confidence: 99%